Comparative study of electrolyte exchange in patients with varying severity of urinary syndrome of chronic pyelonephritis - Gozhenko, Anatoliy; Kushneruk, Anatoliy; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2015)
Background. The severity of urinary syndrome in chronic pyelonephritis varies widely. Concomitant changes in electrolyte exchange are also differently expressed. The aim of this study is to compare the rates of electrolyte metabolism in patients with minimal and moderate manifestations of urinary syndrome. Materials and Methods. The object of clinical-physiological observation were 68 men and 20 women aged 24-76 years, who underwent rehabilitation treatment in the Truskavets’ spa of chronic pyelonephritis in remission with of neuroendocrine-immune complex dysfunction. Urinary syndrome was assessed by quantitative and quantitative-qualitative levels of bacteriuria, leukocyturia and erythrocyturia. We determined in daily urine and blood plasma the concentration of sodium, potassium, chloride, calcium, magnesium and phosphates. Results. By transforming the actual values into normalized (Z-score) in patients with minimal expressed urinary syndrome (n=25) compared with moderately expressed (n=63) more pronounced decrease in phosphatemia (-1,26±0,17 vs -0,77±0,13), while a more significant increase in excretion of magnesium (+1,16±0,34 vs +0,27±0,24), sodium (+2,92±0,64 vs +1,41±0,31) and chloride (+2,44±0,76 vs +1,04±0,37). Conclusion. Probably, common causal factors for both sets of parameters are changes in neuro-endocrine regulation of electrolyte exchange and immunity, especially bactericidal mechanisms, which, in turn, cause a reduction in bacteriuria and leukocyturia, ie resolving chronic pyelonephritis. Evidence of this hypothesis we have obtained and will be presented in the next article.